More evidence on cash transfers and child nutritional outcomes: A systematic review and meta-analysis - Manley, James; Alderman, Harold; Gentilini, Ugo (BMJ, 2022)
Background Cash transfer (CT) programmes are an increasingly common approach to alleviate poverty and inequality and improving child health and nutrition, as well as supporting other goals such as education. Evidence indicates that CTs can be effective, but overall impacts are small in magnitude. This paper substantially updates the evidence base on the effectiveness of CTs and moderating factors. Methods Building on a prior search done in 2018, we searched articles published between January 2018 and March 2021 using Agris, Econlit, Eldis, IBSS, IDEAS, IFPRI, Google Scholar, PubMed and World Bank databases. We included studies using quantitative impact evaluation methods of CTs with sample sizes over 300, targeted to households with children under 5 years conducted with clear counterfactuals in countries with gross domestic product below US$10 000 at baseline. We performed meta-analysis using random effects models to assess the impact of CT programme on selected child nutrition outcomes. Findings Out of 1561 articles identified, 55 additional articles were eligible for inclusion for a total of 129 estimates. We find that CTs have significant although modest effects on height-for-age z-scores (HAZ) (0.024, 95% CI 0.004 to 0.044; p<0.02); stunting (−1.35%, 95% CI −2.35 to − 0.35; p<0;01); wasting (−1.31%, 95% CI −2.16% to 0.46%; p<0.01); animal-source foods (6.72%, 95% CI 5.24% to 8.20%; p<0.01); diet diversity (0.55, 95% CI 0.30 to 0.81; p<0.01) and diarrhoea incidence (− 1.74%, 95% CI −2.79% to −0.68%; p<0.05). There was no significant effect of CTs on weight-for-height (WHZ) or weight-for-age z-scores (WAZ). Well-targeted behaviour change communication was also effective in improving HAZ and decreasing the prevalence of diarrhoea. Interpretation CT programmes improved linear growth among young children, reducing wasting and stunting, but effects are heterogeneous and somewhat small overall. More evidence indicates that effects on dietary diversity and the consumption of animal-source foods are increasingly pronounced.